Physicochemical and Biological Controls on Carbon and Nitrogen in Permafrost from an Ultraxerous Environment, McMurdo Dry Valleys of Antarctica. Issue 10 (17th October 2017) - Faucher, Benoit; Lacelle, Denis; Davila, Alfonso; Pollard, Wayne; Fisher, David; McKay, Christopher P.
Abstract: Little is known about the abundance and source of soil organic carbon and biogeochemical cycling in permafrost soils from the ultraxerous environment of the Dry Valleys of Antarctica. Here we investigate the distribution, source and cycling of organic carbon, total nitrogen and carbonates in the icy permafrost soils of University Valley, Quartermain Mountains. Results indicate that organic carbon content is lowest in icy soils from the perennially cryotic zone (<40 μg g −1 dry soils) and higher in the icy soils from the seasonally noncryotic zone, where the highest concentrations were found in the warmer‐wetter section of the valley and near a frozen pond (up to 313 μg g −1 dry soils). The δ 13 Corg of organic carbon in the icy soils showed that it is derived from the weathering of Beacon Supergroup sandstone that hosts active endolithic communities. The C:N ratios in icy soils formed two populations: one with ratios <5 and the other with ratios near the Redfield ratios. The low C:N ratios suggest that physicochemical processes dominates these soils, as supported by the absence of microbial activity and atmospherically deposited NO3 with minimal postdeposition modification. The near Redfield C:N ratios can be explained by physical processes (translocation of SOC in the soils from snow meltwater) or balanced microbial activity. The latter is supported by the δ 13 CCaCO3 values of carbonates that suggest a contribution from microbially respired endolith‐derived organic matter, providing indirect evidence of heterotrophic activity in permafrost soils from an ultraxerous environment. Key Points: Organic carbon, total nitrogen, and carbonate contents follow ground surface temperature zones and are the lowest reported in the Dry Valleys Organic carbon in the icy soils originates from the weathering of Beacon Supergroup sandstone that hosts active endoliths δ 13 CCaCO3 in some of the icy soils suggests a contribution of microbial respiration of endolith‐derived organic matter